The Effects of Delivery Mode on the Gut Microbiota and Health: State of Art - Zhang, Chenchen; Li, Lixiang; Jin, Biying; Xu, Xinyan; Zuo, Xiuli; Li, Yanqing; Li, Zhen (Frontiers in Microbiology, 2021)
The delivery mode is an important factor driving alteration in the gut microbiota during the neonatal period. Several studies prove that the alteration of gut microbiota induced by cesarean section could influence the activation of intestinal epithelial cells and the development of immune system. Further, some autoimmune and metabolic disorders may be related to the microbiota dysbiosis in infants caused by cesarean section. It is noteworthy that probiotics could promote the intestinal microecology, which may further prevent and treat cesarean section related diseases. This review summarized the great significance of delivery mode on microbiota and health, as well as provided clinically feasible methods for the prevention and treatment of cesarean section related gut diseases.